المعاش النفسي لذى ممرضي مصلحة الاورام السرطانية - فتحي أمينة (كلية العلوم الاجتماعية, 2020)
Abstract : The current study aims to reveal the psychological pension of the Oncology Authority nurses working in the Cancer Control Center in Bechar province. This is done through understanding the stresses and psychological disorders experienced by the oncology department nurses, and identifying the implications of the nursing work for the Cancerous Tumors Authority on the physical and psychological health of the patients. In order to verify the validity of the study hypotheses, we used the clinical approach that includes the case study by using the following techniques : clinical observation, the semi clinical interview directed by relying on the interview guide designed by the researcher. In addition to the use of psychological scales including: the mental health scale, the anxiety scale, whether a transient condition or personality trait of Spielberger and the Liel Brown obsessive-compulsive scale. The basic study lasted from late December 2019 to February 19, 2020, and the study was applied to a sample consisting of 3 cases out of 7 that were chosen intentionally ،their ages range between (22-30). So that the following results were reached: The psychological pension of Cancer Service nurses is characterized by the presence of anxiety related to illness, health, death and the future. The psychological pension of Cancer Care nurses is characterized by the presence of obsessive-compulsive disorder that appears in the form of controlling thoughts about issues related to illness and health
Keywords: مصلحة الاورام السرطانية؛المعاش النفسي